Role of hypothetical protein PA1-LRP in antibacterial activity of endolysin from a new Pantoea phage PA1 - Tian, Ye; Xu, Xinyan; Ijaz, Munazza; Shen, Ying; Shahid, Muhammad Shafiq; Ahmed, Temoor; Ali, Hayssam M.; Yan, Chengqi; Gu, Chunyan; Lu, Jianfei; Wang, Yanli; Ondrasek, Gabrijel; et al. (Frontiers in Microbiology, 2024)
Pantoea ananatis has emerged as a significant plant pathogen affecting various crops worldwide, causing substantial economic losses. Bacteriophages and their endolysins offer promising alternatives for controlling bacterial infections, addressing the growing concerns of antibiotic resistance. This study isolated and characterized a novel Pantoea phage, PA1, belonging to the Chaseviridae family. PA1 exhibited a broad host range against P. ananatis strains, with a latent period of 40 minutes and a burst size of 17.17 phages per infected cell. Genome analysis of PA1 revealed an endolysin, PA1-Lys, which showed lytic activity against various chloroform-treated Gram-negative bacteria.PA1-Lys remained stable at pH 6-10 and temperatures of 20-50°C. While PA1-Lys alone could not directly lyse bacteria, its lytic activity was enhanced in the presence of EDTA. Surprisingly, ORF13 encoded hypothetical protein PA1-LRP was found to inhibit bacterial growth when expressed alone and showed synergistic effects when coexpressed with PA1-Lys. After 24 h of incubation, the OD600 value of pET28a-LRP (28a-LRP) decreased by 0.164 compared to pET28a (28a). Furthermore, the lytic effect of co-expressed PA1-LRP and PA1-Lys was significantly stronger than as compared to PA1-LRP and PA1-Lys expressed separately. After 24 h of incubation, compared to pET28a-LRP (28a-LRP), the OD600 value of pET28a-Lys-LRP (28a-Lys-LRP) decreased by 0.444, while the OD420 value increased by 3.121. Live/dead cell staining, and flow cytometry experiments showed that the fusion expression of PA1-LRP and PA1-Lys resulted in 41.29% cell death, with bacterial morphology changing from rodshaped to filamentous. Notably, PA1-LRP provided stronger support for endolysinmediated cell lysis than exogenous transmembrane domains (TMDs). Additionally, our results demonstrated that the hydrophobic region of PA1-LRP (HPP), when fused with PA1-Lys, led to 40.60% cell death, with bacteria changing from rod-shaped to spherical and exhibiting vacuolation. Taken together, this study provides insights into the lysis mechanisms of Pantoea phages and identifies a novel lysis-related protein, PA1-LRP, which could have potential applications in phage therapy and bacterial disease control.